Bajau Traditional Healing Ritual in Sabah: An Analysis from the Islamic Perspectives - Syamsul Azizul Marinsah; Asmiaty Amat; Aisyah Tamby Omar (2020)
The Bajau is among the largest ethnic groups in Sabah. Most Bajau are Muslims. They can be classified into two different groups namely the Bajau ethnic group from the east coast and west coast of Sabah. They possess a myriad of materials and non-materials from their ancie heritage. Hence, this study aims to document the traditional healing ritual among the Bajau ethnic and analyze whether the rituals are Syariah-compliant. The focus of the study was based on the ‘magombo’ healing rituals of the Bajau from the east coast and the ‘ngalai” healing rituals of the Bajau from the west coast of Sabah. The population of this study included the Bajau ethnic residing in Semporna and Kota Belud. These areas were chosen because they consist of a majority of Bajau ethnic. A qualitative approach using observation, interview and documentation methods were adopted for data collection. The findings revealed that the ‘magombo’ and ‘ngalai’ traditional healing rituals are non-Syariah compliant and fall under the ‘urf fasid’ category.